Currículo prescritivo e disciplinador do estado de São Paulo (2008-2010): Geografia no ensino médio - Lopes, Maria Rita de Castro (2014)
The 2008 curricular reform in the state of São Paulo for primary and secondary education, called Programa São Paulo Faz Escola (SPFE), was systematized into teaching materials named Teacher Notebook and Student Notebook, which show the content, activities, evaluations and other elements that teachers may use in their classes. Due to this significant change in the public teaching of São Paulo this work intends to study the curricular principles of SPFE and how they articulate to the Geography s proposal from secondary education existing in the Teacher and Student s Notebook. Furthermore, it evaluates the geographic contents that are within the secondary education Notebook and reflects about the conception of Geography teaching. To substantiate the curriculum documental analysis it was used the theoretical references developed by Michael W. Apple (1993; 2006), Ivor Goodson (2001) and André Chervel (1990), referring to the conceptions of school, school discipline and curriculum, and finally, Antonio Viñao (2002) for the discussion of curricular reform. Then it could be seen that Geography curriculum of SPFE is based on content learning because it treats geography teaching as a simplification of scientific knowledge and does not contribute to the development of mechanisms to the students understand their geographic reality